2020
DOI: 10.1177/2151459320938571
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Severe Proximal Humerus Fracture and Correlation Between Deltoid Tuberosity Index and Bone Mineral Density

Abstract: Introduction: The aims of this study were to investigate (1) whether demographic factors would be risk factors for severe proximal humerus fracture (PHF), (2) relationship of radiological parameters with bone mineral density (BMD), deltoid tuberosity index (DTI), or severe PHF, and (3) correlation between DTI and BMD. Methods: We conducted a cross-sectional study based on radiographs and medical records ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Similar findings were also revealed in the present study. The present study found that, as age increases by one year, the incidence of severe PHF increases by 1.064 times, this result is comparable to the results (1.044 times) of Kim et al[ 38 ], additionally, they indicated that gender was the independent risk factor of severe PHFs considering that females were 3.763 times more likely to suffer from severe PHF than males, without a clear cause. This study only included patients greater than or equal to 60 years old, here we did not find a similar result.…”
Section: Discussionsupporting
confidence: 90%
“…Similar findings were also revealed in the present study. The present study found that, as age increases by one year, the incidence of severe PHF increases by 1.064 times, this result is comparable to the results (1.044 times) of Kim et al[ 38 ], additionally, they indicated that gender was the independent risk factor of severe PHFs considering that females were 3.763 times more likely to suffer from severe PHF than males, without a clear cause. This study only included patients greater than or equal to 60 years old, here we did not find a similar result.…”
Section: Discussionsupporting
confidence: 90%
“…The Tingart index ( 7 ) and the deltoid tuberosity index ( 8 ) assess cortical bone thickness measurements on anteroposterior views of the shoulder using a 2-dimensional technique. These two methods of measuring cortical bone thickness have been widely investigated in proximal humerus fracture ( 8 , 9 ); however, it has not been determined whether the trabecular thickness (Tb.th) of the humeral trabecular bones change in the process of aging ( 10 ). Dual-energy X-ray absorptiometry (DXA) method remains the gold standard for the diagnosis of osteoporosis, but there is not yet a defined threshold value for the proximal humerus ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…26,27 The DTI value was lower in women in the plate group, which is related to poorer bone quality and predisposition to fractures. The study of Kim et al,28 in 2020, showed a strong correlation between the deltoid tuberosity index (DTI) and the T score value in bone densitometry. Values < 1.4 correlate with low bone mineral density in patients with proximal humerus fracture, and female sex and advanced age were considered independent risk factors for severe proximal humerus fracture.…”
Section: Discussionmentioning
confidence: 99%